Noncompatibility of power and endurance training among college baseball players - Rhea, M. R.; Oliverson, J. R.; Marshall, G.; Peterson, M. D.; Kenn, J. G.; Ayllon, F. N. (The Journal of Strength and Conditioning Research, 2008)
Exercise professionals seeking to develop evidence-based training programs rely on several training principles demonstrated through research and professional experience. In an effort to further research examining these principles, an investigation was designed and completed to evaluate the compatibility of cardiovascular endurance and neuromuscular power training. Sixteen Division-I collegiate baseball players were divided into two training groups with lower body power measured before and after their college playing season. The two groups differed in training in that one group performed moderate- to high-intense cardiovascular endurance training 3-4 days per week throughout the season, while the other group participated in speed/speed endurance training. A significant difference between groups (P < .05) was identified in the change in lower body power during the baseball season. During the season, the endurance training group decreased an average of 39.50 +/- 128.03 watts while the speed group improved an average of 210.63 +/- 168.96 watts. These data demonstrate that moderate- to high-intense cardiovascular endurance and neuromuscular power training do not appear to be compatible when performed simultaneously. For baseball players, athletes who rely heavily on power and speed, conventional baseball conditioning involving significant amounts of cardiovascular endurance training should be altered to include more speed/power interval training.